Pengaruh Crew Change Plan Terhadap Ketidaksesuaian Kontrak Kerja di PT MCS Internasional - Evika Syam Pramesti Putri; Supriyanta Supriyanta (Logistics and Supply Chain Insights, 2025)
The suboptimal crew change plan results in inappropriate crew changes, the crew's work contract does not comply with the Sea Work Agreement (PKL). From this, the author is interested in researching: 1) Delays in the crew change plan 2) The crew's work contract period exceeds the Sea Work Agreement (PKL) 3) Insufficient standby crew at PT MCS Internasional. This study aims to determine the influence of the crew change plan on the incompatibility of the work contract at PT MCS Internasional. The study was conducted for 3 months from February 2023 to May 2023 at PT MCS Internasional. The author uses a quantitative research method with calculation analysis in the form of simple linear regression analysis, t-test and coefficient of determination test. The data collection techniques used are by means of observation, questionnaires, and documentation studies. The respondents who were the subjects of the study were the crew of the Humpus Transportasi Kimia (HTK) tanker totaling 50 respondents. The collected data was processed using the Statistical Package For The Social Sciences (SPSS) version 27. The results of this study are: 1) Crew change plan is a process to determine the replacement/transfer of ship crews who have passed the work contract time limit. 2) The ship's crew at PT MCS Internasional experienced a mismatch in the work contract time because the contract time exceeded the Sea Work Agreement (PKL). 3) Based on a simple linear regression test, there is an influence of variable (X) on variable (Y) with a significance value of 0.000 <0.05 and the regression equation Y = 5.518 + 1.138 (X) is obtained, based on the t test, the results of t count = 8.117> t table = 2.0484 and a determination coefficient of 57% is obtained. It can be concluded that